Generally Accepted Accounting Practice: A South African Viewpoint. - Smith, Charles H.; Burns, Thomas J. (The Accounting Review, 1980)
The article reviews the book "Generally Accepted Accounting Practice: A South African Viewpoint," by G. K. Everingham and B. D. Hopkins.